Sticks & stones - Mlynowski, Sarah; Myracle, Lauren, 1969-; Jenkins, Emily, 1967- (New York : Scholastic Press, 2016)
Nory, Bax, and their friends are in a special class at Dunwiddle Magic School, a class for children whose magic is unpredictable--and while Nory is finding an outlet for her dritten-self (a combination of a kitten and dragon), in the kittenball team, Bax is worried because all he can do is turn into a rock, and nobody knows why.
4.3
3-6
540L
Keywords: Magic -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Fiction; Shapeshifting -- Fiction; Schools -- Fiction; Magic -- Fiction; Shapeshifting -- Fiction; School stories; Magic -- Fiction; Shapeshifting -- Fiction; Schools -- Fiction; Fantasy fiction